MODEL LITERASI FINANSIAL DIGITAL DAN MEDIASI PENGETAHUAN FINANSIAL DALAM KEPUTUSAN INVESTASI: STUDI PADA GENERASI Z DI LAMPUNG - Pariyanti, Eka; Desastra, Yolla Zelika; Rinannik, Rinannik (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to examine the effect of Digital Financial Literacy (DFL) on Financial Knowledge (FK) and Investment Decision (ID) among Generation Z in Indonesia, as well as the mediating role of financial knowledge in this relationship. Data were collected through questionnaires from 101 Generation Z respondents who actively use digital platforms for financial management and investment. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) through regression and correlation analysis. The results indicate that Digital Financial Literacy positively influences both Financial Knowledge and Investment Decision. Furthermore, Financial Knowledge positively affects Investment Decision and mediates the relationship between Digital Financial Literacy and Investment Decision. These findings highlight the importance of digital financial literacy and financial knowledge as key factors in supporting informed investment decisions among Generation Z.